Effects of the covid-19 pandemic on the marine mammal tourism of Walvis Bay, Namibia - Mataranyika, Panashe Valentina (University of the Philippines Visayas, 2021)
The COVID-19 pandemic has as had a major impact on many different sectors across the world and even with the development of a vaccine there is no end in sight as yet. The marine mammal tourism industry is one of the sectors that has been heavily affected by the restrictions in international travel and and social distancing and the effect the pandemic has had on the major stakeholders in the marine mammal tourism industry in Walvis Bay, Namibia through the use of secondary data, key informant interviews and a focusgroup discussion with the tour operators, community members, the environmental organizations and the Namibia Tourism Board that governs the industry. The methods sought to discover if the new protocols have negatively affected income for the tour operators, employment for the locals and if there has een a positive impact on the environment as seen in other countries where commercial vessel traffic has been significantly reduced due to pandemic. The results show that the effects of the pandemic are both positive and negative and there is room for further discussion on how the new procedures may be adapted or adjusted in a sustainable manner for all the staakeholders involved. A key problem that was brought to attention in this study is the poor governance and lack of regulation within the industry three decades after it was first initiated and the lack of community involvement. In conclusion the pandemic has highlighted the short comings within the MMT industry snd also introduced protocols that will likely be maintained in the future that would likely slow the spread in the case of any future viruses or outbreaks.